Reperfusion Arrhythmia in Acute Myocardial Infarction: Clinical Implication and Management - Harris Kristanto; Budi Satrijo; Sasmojo Widito; Ardian Rizal (Universitas Brawijaya, 2022)
Reperfusion is a critical component of myocardium survival in acute myocardial infarction to minimize infarct size and improve clinical prognosis. Reperfusion, on the other hand, may result in increased and accelerated myocardial injury, a condition known as reperfusion injury. Following reperfusion, several arrhythmias are observed, and it is called reperfusion arrhythmia. Reperfusion arrhythmia is one manifestation of reperfusion injury. Numerous modest studies have evaluated what reperfusion arrhythmias are defined. It is described as an arrhythmia that occurs immediately or within the first minutes after coronary blood flow is restored. Traditionally, Accelerated Idioventricular Rhythm (AIVR) has been seen as a reperfusion arrhythmia. However, reperfusion may reveal any arrhythmia (or none at all); conversely, AIVR may occur in the absence of reperfusion. Calcium excess within the cells is thought to be a significant factor in the development of reperfusion arrhythmias. This may affect the significant delay following depolarization and the regional heterogeneity of regional blood flow restoration inside the ischemic zone, resulting in reperfusion arrhythmia. In some studies, it was mentioned that these arrhythmias may be due to ongoing myocardial cell damage and ischemia. Arrhythmias associated with reperfusion require special attention since hemodynamics can deteriorate quickly. In this review, clinical significance and management of reperfusion arrhythmia, as well as its link with reperfusion injury will be discussed.